The complete mitochondrial genome of Black-streaked Scimitar Babbler Pomatorhinus dedekeni (Passeriformes: Timaliidae). Issue 2 (2nd April 2020) - Yang, Nan; Wu, Yong; Qiao, Lu; Zhao, Ding; Yang, Kong
Abstract: In this research, we determined and described the complete mitochondrial genome of Black-streaked Scimitar Babbler ( Pomatorhinus dedekeni ) which was the first complete mitogenome reported. The complete genome of P. dedekeni was 16, 996 bp in length and contained 13 protein-coding genes, 22 transfer RNA genes, two ribosome RNA genes, and one non-coding control region. The overall base composition of the mitochondrial DNA was 29.2% for A, 22.9% for T, 14.6% for G, and 33.3% for C, with a GC content of 47.9%. The information of P. dedekeni will contribute to the phylogenetic studies of the Timaliidae.